Public awareness and practices towards self-medication with antibiotics among the Malaysian population. A development of questionnaire and pilot-testing - Aslam, Adeel; Gajdács,, Márió; Zin, Che Suraya; Ab Rahman, Norny Syafinaz; Ahmed, Syed Imran; Jamshed, Shazia Qasim (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
It is well documented that injudicious antibiotic use and practicing self-medication with antibiotics (SMA) can lead to antibiotic resistance. The objective was to validate and develop an instrument in Bahasa Melayu to assess the awareness and practices towards SMA in the Malaysian population. A pilot study was conducted among 100 Malaysians participants. Reliability testing in terms of test-retest, internal consistency, and content validity was performed. One-way ANOVA and t-test were applied to determine significant differences between groups. A panel of nine experts evaluated the research instrument for content validity and it was found to have strong content item validity (Indices = 1). Each domain (level of knowledge and understanding about antibiotic use and antibiotic resistance: Practice towards self-medication) showed good internal consistency of Cronbach’s alpha 0.658 and 0.90. While test-retest reliability value for each domain was 0.773 (p = 0.009), and 0.891 (p = 0.001. The mean ± standard deviation (SD) for level of knowledge about antibiotic use and antibiotic resistance was 21.8 ± 7.02 and for practice scores (SMA) 6.03 ± 2.30. The instrument established sound reliability and validity and, therefore, can be an effective tool for assessing public awareness, and practices toward self-medication with antibiotics in the Malaysian population. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.